Resepsi dan Transmisi Nilai-Nilai Hidup Qurani Berbasis Kearifan Lokal Dalam Syi’ir Nyai Maryam - Asy'ari, Jihan Adibah; Kafid, Nur (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2023)
This research based on the tradition of reviving the Qur'an through syi'ir. The values of life contained in Nyai Maryam's syi'ir are the substance of the Qur'an doctrine. This syi'ir was created by Nyai Maryam as a medium in teaching the Qur'an. So this research aims to describe the transmission process of Nyai Maryam's syi'ir and find out the reception of the use of Nyai Maryam's syi'ir in religious activities created from Nyai Maryam's interpretation of the Qur'an. This research is a qualitative research with a type of field research that uses the Living Quran approach and triangulation data validity. Data is obtained through data collection techniques such as interviews, observation, and documentation. The primary source of this research is Nyai Maryam's syi'ir contained in the book Maulidul Barzanji Natsron which is supported by secondary sources from several books, journals and previous scientific works. The data analysis technique used in this research is data reduction by choosing and selecting any incoming data from the results of interviews, observations and documentation. The research findings are the teachings contained in the syi'ir regarding adab towards the Qur'an and the values of life that remind readers of the importance of maintaining adab towards the Qur'an. The practice of reciting this syi'ir is still preserved until the current generation in various religious activities.